The politics of resentment : British Columbia regionalism and Canadian unity - Resnick, Philip (desLibris. Books collection., 2000)
"The Politics of Resentment is the first book to examine the role that British Columbia has played in the evolving Canadian unity debate. Philip Resnick explores what makes British Columbia stand apart as a region of Canada. He looks at the views of politicians, opinionmakers, and ordinary British Columbians on their sense of estrangement from central Canada, on the challenges posed by Quebec nationalism, and on what they see as the future of Canadian unity. He concludes with an examination of the likely BC response in the event of a "yes" vote in any future Quebec referendum on sovereignty." "The Politics of Resentment provides a new way of thinking about British Columbia's place within the Canadian federation. It draws on a wide range of sources - government documents and media sources, the work of BC authors and commentators, and academic literature on regionalism and nationalism - to capture what underlies the often-fractured relationship between Canada's westernmost province and the rest of the country."--Jacket